The capital market of deveoping country / Nigeria, a case study (London The pennsylvania state university, 1982)
This thesis examines the state of the capital market of s developing country, with emphasis to Nigeria as a case study.
asm; 06/02/20
Loans
Keywords: Economist; Stock exchanges; Financial economist; Developing coutry; Nigeria